2021
DOI: 10.1186/s12935-020-01735-5
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide kinase mediates intrinsic resistance and inferior response to chemotherapy in triple‐negative breast cancer by upregulating Ras/ERK and PI3K/Akt pathways

Abstract: Background Clinical management of triple-negative breast cancer (TNBC) patients remain challenging because of the development of chemo-resistance. Identification of biomarkers for risk stratification of chemo-resistance and therapeutic decision-making to overcome such resistance is thus necessary. Methods Retrospective analysis was performed to identify potential stratification biomarkers. The levels of ceramide kinase (CERK) was determined in brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Multiple studies suggest that the Ras pathway may influence the behavior of TNBC and HGSOC. For instance, Zhu and colleagues recently reported a correlation between Ras/ERK upregulation and chemoresistance in TNBC [ 70 , 71 ]. In the present series, we could not find any differences in the mutation rate of the Ras signaling pathway-related genes while comparing age and cancer type groups.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies suggest that the Ras pathway may influence the behavior of TNBC and HGSOC. For instance, Zhu and colleagues recently reported a correlation between Ras/ERK upregulation and chemoresistance in TNBC [ 70 , 71 ]. In the present series, we could not find any differences in the mutation rate of the Ras signaling pathway-related genes while comparing age and cancer type groups.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, CERK overexpression showed to be a biomarker for chemotherapeutic response in TNBC and higher than two-fold change in CERK (from tumor)/CERK (from normal counterpart) ratio was significantly linked to chemoresistance to doxorubicin and paclitaxel (OR = 2.66, 95% CI 1.18-7.34), p = 0.04. CERK overexpression conferred chemoresistance in TNBC cell lines that CERK inhibition allowed to overcome; mechanistic studies suggest that CERK mediates intrinsic resistance and lower response to CT in TNBC by governing several oncogenic pathways such as Ras (rat sarcoma virus)/ERK (extracellular signal-regulated kinase), PI3K/Akt/mTOR, and Ras homolog family member A (RhoA) [149].…”
Section: Brcanessmentioning
confidence: 99%
“…Of interest, it was also reported that estrogen receptor-negative breast cancer patients with high CERK expression exhibited worse prognosis [ 67 ]. Moreover, CERK overexpression was sufficient to promote triple-negative breast cancer (TNBC) cell growth and migration, and conferred chemoresistance to TNBC cell lines [ 68 ]. Moreover, inhibition of CERK counteracted chemoresistance in the breast cancer cells through a mechanism involving activation of the Ras/ERK, PI3K/Akt/mTOR, and RhoA pathways [ 68 , 69 ].…”
Section: Implication Of Cerk/c1p In Breast Cancermentioning
confidence: 99%